2003
DOI: 10.1097/00004872-200312000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Circulating coupling factor 6 in human hypertension

Abstract: These indicate that circulating coupling factor 6 is elevated in human hypertension and modulated by salt intake presumably via reactive oxygen species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…Intracellular acidosis increases constrictor tone, in association with simultaneous increases in cytosolic free Ca 2+ , as reported in barnacle and frog muscle fibres [11,12]. We and others, moreover, have demonstrated that plasma levels of CF6 were increased in patients with hypertension and diabetes [13,14]. Overall, the above suggests that CF6 might contribute to diabetes and hypertension by intracellular acidosis.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Intracellular acidosis increases constrictor tone, in association with simultaneous increases in cytosolic free Ca 2+ , as reported in barnacle and frog muscle fibres [11,12]. We and others, moreover, have demonstrated that plasma levels of CF6 were increased in patients with hypertension and diabetes [13,14]. Overall, the above suggests that CF6 might contribute to diabetes and hypertension by intracellular acidosis.…”
Section: Introductionsupporting
confidence: 77%
“…2c). We and others had previously reported that the plasma level of CF6 was increased by twofold in patients with coronary heart disease, hypertension, end-stage renal disease and stroke, compared with that in healthy participants [13,[16][17][18][19]]. Thus, the plasma level of CF6 in transgenic mice was noted to be increased as compared with wild-type mice to a degree similar to that seen in patients with cardiovascular diseases.…”
Section: Resultsmentioning
confidence: 59%
“…Given the present finding and the widespread biological actions of CF6, such as inhibition of prostacyclin and NO (8,9), reduction in CF6 levels may be important and useful to prevent arteriosclerosis and eventually cardiovascular events. To date, we have reported that salt restriction, vitamin C, and vitamin B 12 plus folic acid lower the plasma CF6 levels of patients with hypertension and stroke (13,14) and that peroxisome proliferator-activated receptor  ligand attenuate CF6 release from cultured vascular endothelial cells (33). Thus, the present findings may provide new insights into our understanding of the pivotal role played by CF6 in the mechanism underlying endothelial dysfunction.…”
Section: Implications Of Linkage Between Cf6 and Cxcr4 In Cardiovascusupporting
confidence: 52%
“…Figure 4A illustrates the representative bands for CXCR4 proteins in the hearts of TG and WT at 50 weeks of age. The immunoreactive band for CXCR4 at 40-47kD was decreased in the TG hearts compared with the WT hearts, and the ratio of CXCR4 to CF6 decreased the gene and protein expression of CXCR4, but the decrease was only significant at a concentration of more than 10 -7 M. Like other vasoactive substances, the plasma CF6 level (10 -9 -10 -8 M) was lower than the critical concentration (10 -7 M) at which CXCR4 expression in cultured vascular endothelial cells was decreased in vitro (13,14). We previously showed that intravenous administration of anti-CF6 antibody to rats counteracted the biological effects of CF6 (15).…”
Section: Effect Of Cf6 On Hypoxia-induced Apoptosis In Huvecmentioning
confidence: 85%
See 1 more Smart Citation